Optimizing Performance: The Impact of a 10-Day High-Intensity Interval Training Protocol on Youth Athletic Performance - Milaim Berisha; Era Deva; Aydın Karaçam; Bekir Erhan Orhan (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to examine the impact of a 10-day High-Intensity Interval Training (HIIT) protocol on the specific endurance of U16 female basketball players, focusing on improvements in aerobic and anaerobic capacity and performance in the Yo-Yo Intermittent Recovery Test Level 1 (YoYoRL1).